The Practice of Cramming among Pre-Clinical Medical Students and Their Remedial Examination Result: A Simple Preliminary Demographic Analysis - , Lusia Sri Sunarti; , Yusias Hikmat Diani; , Muhammad Alfarabi; , Jap Mai Cing; , Evy Suryani Arodes; , Linggom Kurniaty; , Forman Erwin Siagian; , Alifa Hasna Ramadhani Fachly (Archives of Current Research International, 2022)
Aims: To analyze the practice of cramming among pre-clinical medical students during the remedial examination based on their gender and place of residence, along with a review of the literature on the factors that foster this practice. Study Design: Simple cross-sectional study. Place and Duration of Study: Faculty of Medicine, Universitas Kristen Indonesia, Jakarta- Indonesia, throughout August 2022. Methodology: Analysis of demographics data, gender and place of residence, of the cramming and non-cramming students, with the results of total 36 remedial exam scores for courses/block in the second, fourth, and sixth semesters. Results: Out of 2413, 739 (30.62%) were male and 1674 (69.37%) were female, and 1054 (43.68%) live in boarding houses and 1359 (56.31%) live in their own private house. Cramming conducted by 1553 students (64.35%) consisting of 505 males (32.51%) and 1049 female (67.54%). Based on the total number of participants taking the remedial exam, the prevalence of cramming was slightly higher in male student (68.33%) compared to female student (62.66%). Based on their place of residence, most of the perpetrator live in their own house (n=935 or 60.20%) and 39.80% live in boarding houses (n=619). Statistic analysis using Pearson chi-square on the gender differences and place of residence in cramming behavior both were proved significant (P=0.007 and P=0.000). The average passing percentage of cramming perpetrator is only 43.13% with very low mean score (50.13). There is a reduction in the prevalence of cramming as the students reach higher level of education. Conclusion: Cramming among medical students still a common practice although the success story regarding this activity is still questionable because there are still more perpetrators who fail the exam and do not reach the lower threshold value of passing.